Synthesis, Structural Characterization of a New Ni(II) Complex and Its Catalytic Activity for Oxidation of Benzyl Alcohol - Li-Hua Wang; Fan-Yuan Kong; Xi-Shi Tai (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
In ethanol-water (v:v = 1:1), a new Ni(II) complex, [Ni(L)2(H2O)2] (1) (HL = 6-phenylpyridine-2-carboxylic acid) was synthesized using 6-phenylpyridine-2-carboxylic acid, NaOH and Ni(CH3COO)2.4H2O. The structure of complex 1 has been determined by elemental analysis and single crystal X-ray diffraction. The single crystal analysis shows that complex 1 contains one Ni(II) ion, two L ligands and  two coordinated water molecules. In 1, the Ni(II) ion is six-coordinated to two O atoms and two N atoms from L ligands and two O atoms from coordinated water molecules, respectively, which form a distorted octahedral coordination geometry. The whole unit of complex 1 is interconnected to each other through intermolecular N−H•••O hydrogen bonds involving oxygen atom of coordinated water molecule and the oxygen atoms of  L ligand to form 1D molecular architecture. The catalytic activity of complex 1 for oxidation of benzyl alcohol with O2 was investigated. The complex 1 shows good catalytic performance for the oxidation of benzyl alcohol, the benzyl alcohol conversion, benzaldehyde selectivity, and benzaldehyde yield were 49.1%, 92.0%, and 45.2%, respectively, at 90 °C under 0.7 Mpa O2 for 2 h. Moreover, complex 1 could be recovered easily by centrifugation and used repetitively for at least four times. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).